Decision making and design in structural engineering problems under polymorphic uncertainty. (15th March 2021) - Drieschner, Martin; Petryna, Yuri; Freitag, Steffen; Edler, Philipp; Schmidt, Albrecht; Lahmer, Tom
Abstract: The treatment of diverse uncertainties is an important challenge in structural engineering problems, especially from the viewpoint of realistic analysis. Inaccuracy and variability are always present and have to be quantified by either probabilistic, possibilistic, polymorphic or other approaches. Regardless of the applied uncertainty quantification method, the numerical predictions have to be useful for decision making and design. In this contribution, the authors present three individual solutions concerning a benchmark example of a portal frame structure including various uncertainties. A focus is set on the quantification of epistemic uncertainties which differ and influence the obtained decision outcomes. It is proposed to assess the structure conservatively based on a worst case scenario to guarantee the fulfillment of given constraints on the one hand and to compare the individual approaches on the other hand.